Development of an assessment framework for student engagement in design thinking projects for health innovation - Dikgomo, Kagiso (Division of Biomedical Engineering, 2021)
Student engagement is a dynamic and multifaceted concept – it encompasses physical, emotional, and cognitive components. Various instruments to assess student engagement exist, however these are not intended to assess how students engage with one another and with community stakeholders in participatory health projects. Although instruments do exist to assess participation/power-sharing in participatory health projects, none of the available instruments are suitable for the assessment of student engagement in such projects. The current study set out to develop an assessment framework for student engagement in design thinking projects for health innovation. Design thinking is a human-centred and participatory approach to problem-solving. The objectives of the project were: (1) the design and implementation of a questionnaire to assess student engagement in design thinking activities, and (2) assessment of the validity of the questionnaire. A preliminary questionnaire was developed with the aid of the literature and implemented for students taking a postgraduate course called Health Innovation & Design, which follows a design thinking approach for health innovation. Analysis of students’ written reflective reports and a focus group discussion were used to revise the questionnaire items. The revised questionnaire was validated by design thinking practitioners (the course lecturer and facilitators), and further modifications were made based on their views. The assessment framework developed in this study incorporates the design thinking phases according to the IDEO design thinking approach, an educational definition of student engagement, and recommendations by students of the Health Innovation & Design course and their course lecturer and facilitators. This questionnaire may be used to assess engagement in academic settings as well as non-academic settings when design thinking is applied for health innovation.